2012
DOI: 10.1590/s1516-18462012005000090
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de maloclusão em escolares de 5 a 12 anos de rede municipal de ensino de Araraquara

Abstract: OBJETIVO: avaliar a prevalência de maloclusões em escolares na faixa etária de cinco a 12 anos, matriculadas em escolas municipais de Araraquara. MÉTODO: com base no número total de crianças (7235) realizou-se o cálculo da amostragem, envolvendo sete escolas, num total de 3380 crianças. Um estudo piloto e a calibração dos examinadores precederam o início da pesquisa. Foram excluídas 1934 crianças da amostra por não atenderem aos critérios de inclusão. Na avaliação clínica, foram analisados, as relações inter-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
(23 reference statements)
5
4
2
3
Order By: Relevance
“…The rate of malocclusions was similar to that of other studies evaluating children in general 13,14 . The prevalence of increased overbite in the general population of children is lower 13,14 than that in the present study; this as, therefore, the only characteristic that distinguished the group of mouth breathers.…”
Section: Discussionsupporting
confidence: 87%
“…The rate of malocclusions was similar to that of other studies evaluating children in general 13,14 . The prevalence of increased overbite in the general population of children is lower 13,14 than that in the present study; this as, therefore, the only characteristic that distinguished the group of mouth breathers.…”
Section: Discussionsupporting
confidence: 87%
“…This prevalence was different in other studies that pointed out rates ranging from 35.05% 36 to 88.68% 19 . Borges 37 mentions that excessive spacing between teeth is not commonly found in mixed dentition, except when there is a protrusion of incisors, which confirms the analysis of the present research.…”
Section: Discussioncontrasting
confidence: 96%
“…In the current sample, the most frequent malocclusion was crowding, which was found in 34.4% of the cases and is within the range reported by other studies -18.05% to 87% [18][19][20][21] . This prevalence was already expected because, according to Peres 9 , such malocclusion is most often associated with Class I molar relationship.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The existent epidemiological studies conducted in Brazil have indicated that the larger portion of children in the mixed dentition stage present some type of morphological deviation in occlusion that varies between 66.00% and 96.80% 1,4,[6][7][8]10,[12][13][14][15][16][17][18][19] and are defined as malocclusion. High rates are expected in this age group, since the intense occlusal changes and exchanges of teeth occur in this period 1 .…”
Section: Discussionmentioning
confidence: 99%